Encyclopaedia of anti-terrorism and security law in India (New Delhi Pentagon, 2009)
The 26/11 Mumbai terror attack has exacerbated the trauma of terror not only in India but all over the world and increased the national demand that our Anti-terror machinery as well as laws need urgent enhancement if the scourge is to be tackled head on. We need not just laws that lend substance to our emerging anti-terror strategies but more importantly, a whole new generation of people who must be educated on what it means to fight terror in a democratic set up. Encyclopedia of Anti-Terrorism and Security Laws of India is exclusively tailored to educated the reader on Terrorism in India and other security related Acts and Rules in clinical detail-through a legal lens. It will effectively serve the purpose of being a ''One stop shop'' for accessing Indian Security Act and Rules. In other words, it acts as a handy logically sequenced, easy to read reference book for acts and rules promulgated in India over time. The encyclopedia is divided in three parts. Encyclopedia of Anti-Terrorism and Security Laws of India provides comprehensive coverage of Indian terrorism and security relation legislation. This Encyclopedia will prove to be a milestone in providing one stop access on the issue of terrorism and security legislation in India.
Keywords: Law; Criminal Law; law on Terriosim; Maj Gen Raj Mehta (ed.)